Ectoparasite extinction in simplified lizard assemblages during experimental island invasion. (26th August 2020) - Cox, Christian L.; Alexander, Sean; Casement, Brianna; Chung, Albert K.; Curlis, John David; Degon, Zachariah; Dubois, Madeline; Falvey, Cleo; Graham, Zackary A.; Folfas, Edita; Gallegos Koyner, Maria A.; Neel, Lauren K.; et al.
Abstract : Introduced species can become invasive, damaging ecosystems and disrupting economies through explosive population growth. One mechanism underlying population expansion in invasive populations is 'enemy release', whereby the invader experiences relaxation of agonistic interactions with other species, including parasites. However, direct observational evidence of release from parasitism during invasion is rare. We mimicked the early stages of invasion by experimentally translocating populations of mite-parasitized slender anole lizards ( Anolis apletophallus ) to islands that varied in the number of native anoles. Two islands were anole-free prior to the introduction, whereas a third island had a resident population of Gaige's anole ( Anolis gaigei ). We then characterized changes in trombiculid mite parasitism over multiple generations post-introduction. We found that mites rapidly went extinct on one-species islands, but that lizards introduced to the two-species island retained mites. After three generations, the two-species island had the highest total density and biomass of lizards, but the lowest density of the introduced species, implying that the 'invasion' had been less successful. This field-transplant study suggests that native species can be 'enemy reservoirs' that facilitate co-colonization of ectoparasites with the invasive host. Broadly, these results indicate that the presence of intact and diverse native communities may help to curb invasiveness.